Plasma indicators of bovine health: Impacts of diet supplementations and pre-slaughter stress - Mylène Delosière; Agnès Thomas; Claudia Terlouw; Denis Durand (Data in Brief, 2018)
This data article reports the values of indicators of bovine health determined in the plasma of Normand cull-cows at different times of the about 100 days lasting finishing period and at slaughter. The data constitute a large dataset based on the quantification of metabolites and the evaluation of enzymes activities allowing the determination of antioxidant capacity, oxidative stress level, energy and lipid metabolisms, activity of the Hypothalamo-Pituitary-Adrenal axis and the hepatic status in cull-cows. Keywords: Cows, Plasma, Health, Diet, Stress